Season of the witch - Brennan, Sarah Rees (New York, NY : Scholastic Inc., 2019)
The summer before her sixteenth birthday, Sabrina Spellman prepares to leave the mortal world behind when a mysterious wood spirit's spell forces her to make a difficult choice.
Keywords: Spellman, Sabrina -- (Fictitious character) -- Juvenile fiction; Witches -- Juvenile fiction; Magic -- Juvenile fiction; Young adult fiction; Fantasy fiction